An asymptomatic multiple magnet ingestion with transmesenteric entero-enteric fistula. - Pederiva, Federica; Daniela, Codrich; Scarpa, Maria-Grazia; Guida, Edoardo; Dragovic, Danica; Martelossi, Stefano (APSP J Case Rep, 2014)
Ingestion of foreign bodies is a common presenting complaint in the pediatric emergency department. We present a case of a child in whom disc battery ingestion was suspected initially. The immobility of the foreign body on few days of conservative management raised the suspicion of two magnets. At operation, two magnets were found in the bowel causing a transmesenteric entero-enteric fistula.